Participation in Fadama User Groups (FUGs) as a medium of social capital and empowerment in Kankara local community, Katsina state-Nigeria - Aminu Rilwanu,; Redzuan, Ma'rof; Abu Samah, Asnarulkhadi (International Organization Of Scientific Research, 2014)
This paper was written to entails the results collected after conducting an empirical research which focus on Participation in Fadama User Groups (FUGs) as a medium of social capital and empowerment in Kankara local community, Katsina state Nigeria. This research was conducted because of the problems observed in the local community of low social capital and empowerment among the Fadama members'. The aim and objective here is to explore the level and relationships in participation, social capital and empowerment among the Fadama members'. The research work also try to explore how participation and social capital can transgress to empowerment.